WANPRESTASI DALAM KONTRAK KONSTRUKSI PROYEK PEMERINTAH YANG DIBIAYAI APBN/APBD - Yanti Yanti; Sarwono Hardjomuljadi; Dwi Edi (Departement of Civil Engineering, Universitas Winaya Mukti, 2026)
Construction contract disputes in government projects funded thru the State Revenue and Expenditure Budget (APBN) and the Regional Revenue and Expenditure Budget (APBD) are legal issues that frequently occur and have wide-ranging implications for public interests. One of the dominant forms of disputes is default in the execution of construction contracts, whether committed by the service provider or the service user. This research aims to analyze the characteristics of default in government project construction contracts and to examine the legal considerations of the Supreme Court in Decision Number 171 PK/PDT/2025. This research uses a normative legal research method with an approach based on legislation, conceptual, and case approaches. The scope of this research is limited to the analysis of default in construction contracts for government projects funded by the state budget (APBN/APBD) and the legal considerations of the Supreme Court at the review stage, without discussing the technical aspects of construction or the overall procurement process of goods and services. The research results show that default in government construction contracts has complex characteristics because it lies at the intersection of civil law and public law. The Supreme Court in that ruling consistently applied the principle of legal certainty and the principle of pacta sunt servanda by limiting the scope of the Review process to the aspect of law application. This decision has important implications in strengthening legal certainty and providing guidance for the parties involved in the implementation of construction contracts for government projects funded by the state budget (APBN/APBD).